PERLINDUNGAN HUKUM TERHADAP DEBITUR ATAS AKTA CESSIE YANG DILAKSANAKAN SEPIHAK OLEH KREDITUR (STUDI KASUS PUTUSAN No. 53/ Pdt.G/2018/PN Gpr. DAN PUTUSAN No. 21/ Pdt.G/2019/PN Kdr) - Yusvaldi, Rhonny; Azheri, Busyra; Adelina Mannas, Yussy (UNES Law Review, 2023)
According to Article 613 paragraph (1) of the Civil Code, it is stated that the surrender of receivables on behalf of and other incorporeal objects are carried out by making an authentic deed and/or private deed, by which the rights to the object are delegated to another person. In a cessie, the takeover of bank receivables by a third party does not mean that only the receivables are taken over, but is accompanied by the takeover of the bank's rights and obligations, including the transfer of collateral for the debtor's debt. The research method used in this study is a Normative Juridical approach, the research results obtained are 1. As a result of the Cessie Deed being carried out unilaterally by the creditor, the Jessie is carried out by making an authentic deed or private deed, the Jessie is transferred by the creditor, and there will be a replacement of the creditor only if the cassie is carried out by Article 613 of the Civil Code, but if the cassie is carried out unilaterally by the creditor then the cassie deed has no legal consequences because the cassie in the deed does not fulfill one of the elements of Article 613 of the Civil Code 2. In case, the taking over of a receivables bank by a third party does not mean that only the receivables are taken over, but it is accompanied by the takeover of the rights and obligations of the bank, including the transfer of collateral for the debtor's debt. The transfer of receivables by Jessie does not result in the termination of the existing agreement made between the creditor and the debtor. 3. The debtor's legal protection for a session which is carried out unilaterally by the creditor according to the Civil Code Article 613 such submission to the debtor has no consequences unless the delivery is notified to him or in writing it is approved and acknowledged if the cassie is carried out unilaterally by the creditor the Jessie has not resulted in the debtor, in other words, the Jessie has not occurred or has not been transferred and the debtor can file a lawsuit in court.